Perancangan Sistem Informasi Kasir menggunakan Kodular di Citra Swalayan Padang - Firdinal Juliandre; Sularno (GLOBAL SCIENTS PUBLISHER, 2024)
This research aims to design a Cashier Information System using the Kodular platform for Citra Swalayan Padang, addressing challenges in managing daily transactions prone to data loss and errors due to manual processes. With a computerized cashier information system, all transactions are expected to be recorded and managed automatically, enhancing operational efficiency and shopping experience for customers with faster, accurate, and integrated information.